KOMPARASI KINERJA PERBANKAN SYARIAH INDONESIA DAN MALAYSIA DENGAN PENDEKATAN MAQASHID SYARI’AH INDEX (MSI) (Studi Pada Perbankan Syariah Indonesia dan Malaysia Tahun 2011-2015) - Luana Devi, Amalia Tery; Fitriyah, Fitriyah (Fakultas Ekonomi, UIN Maliki Malang, 2017)
Abstract: Measuring the performance of sharia banking by using conventional measurement has not beenable to show the assessment of Islamic banking performance in accordance with the purpose of sharia. Thereare differences in sharia banking with conventional banking, so it needs performance measurement from otherside that is devoted to sharia banking. This research aimed at analyzing and comparing the performance ofIslamic banking in Indonesia and Malaysia by using Maqashid Syariah Index (MSI) approach. This researchobject of 11 Sharia Commercial Banks in Indonesia and 15 Sharia Commercial Banks in Malaysia that havebeen operating during 2011-2015. Sources of research data used annual reports of each bank. The steps tomeasure bank performance with Maqashid Syariah Index (MSI) is ratio performance assessment, assessmentof performance indicators and last assessment of the Maqashid Syariah Index (MSI). The results showed thatthere were differences in performance based on the value of Maqasid Syariah Index (MSI) between Indonesianand Malaysian sharia banks in 2011-2015. Sharia banking performance in Indonesia was better in achievingmaqashid sharia than sharia banking in Malaysia. The highest rating of Islamic banking in Indonesia wasPanin Syariah Bank (BPS) and Islamic banking in Malaysia was HSBC Amanah Malaysia Berhad (HSBC)